TERRITORIAL ORGANIZATION OP TOURIST INFRASTRUCTURE IN THE SOUTH OF RUSSIA - O. V. Ivlieva; A. V. Shmytkova (Наука. Инновации. Технологии, 2022)
Introduction. The study aims to analyze and summarize data on the current status of the development of tourist infrastructure of the South of Russia. The analysis of the territorial organization of accommodation establishments, catering facilities and transport infrastructure of the region is presented. The significance of the study of tourism infrastructure in the South of Russia is substantiated. Materials and methods. The study is based on a compilation of official statistics of the Federal State Statistics Service using cartographic and geoinformation modeling methods. The following indicators were selected as mapped indicators: the number of places in accommodation establishments and catering facilities per capita, as well as the density of public roads of local importance owned by the municipality. Discussion of the research results. As a result, the most “weak spots” of the tourist infrastructure in the territorial aspect and the “growth poles” were identified. Conclusions are presented on the main trends in the development of collective accommodation establishments and catering facilities in the South of Russia, the main patterns of development of the transport complex of the macroregion are revealed. Findings. The GIS-based analysis of the territorial organization of tourist infrastructure in the South of Russia allows us to identify: the development of coastal territories as “growth poles”; focal nature of the localization of accommodation and catering establishments in the mountainous territories; involvement in the recreational use of the Volga-Akhtuba floodplain; uneven transport development of the eastern and southwestern regions of southern Russia.